2016
DOI: 10.1159/000447859
|View full text |Cite
|
Sign up to set email alerts
|

B7-H3 Overexpression Predicts Poor Survival of Cancer Patients: A Meta-Analysis

Abstract: Background: B7-H3 exhibits altered expression in various cancers. However, the correlation between B7-H3 expression and prognosis of cancer patients remains controversial. Therefore, we elicit a meta-analysis to investigate the potential value of B7-H3 in the prognostic prediction in human cancers. Materials and Methods: We searched PubMed (last update by June 15th, 2016) to identify studies assessing the effect of B7-H3 on survival of cancer patients. Hazard ratios (HRs) for overall survival (OS), recurrence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 58 publications
1
31
0
Order By: Relevance
“…There is a limited expression of B7-H3 on various normal tissues such as pancreas, liver, small intestine, colon, heart, thymus, spleen, placenta, and testis (357). However, aberrant expression of B7-H3 is seen in various malignancies in which it is associated with poor outcome, including RCC, breast cancer, lung cancer, esophageal squamous cancer, gastric cancer, pancreatic cancer, gallbladder cancer, colorectal cancer, prostate cancer, ovarian cancer, cervical cancer, endometrial cancer, osteosarcoma, and neuroblastoma (358,359). Circulating serum B7-H3 levels are significantly higher in patients with lung cancer, renal cell carcinoma, hepatocellular carcinoma, colorectal carcinoma, and glioma than in healthy volunteers (360).…”
Section: B7-h3mentioning
confidence: 99%
“…There is a limited expression of B7-H3 on various normal tissues such as pancreas, liver, small intestine, colon, heart, thymus, spleen, placenta, and testis (357). However, aberrant expression of B7-H3 is seen in various malignancies in which it is associated with poor outcome, including RCC, breast cancer, lung cancer, esophageal squamous cancer, gastric cancer, pancreatic cancer, gallbladder cancer, colorectal cancer, prostate cancer, ovarian cancer, cervical cancer, endometrial cancer, osteosarcoma, and neuroblastoma (358,359). Circulating serum B7-H3 levels are significantly higher in patients with lung cancer, renal cell carcinoma, hepatocellular carcinoma, colorectal carcinoma, and glioma than in healthy volunteers (360).…”
Section: B7-h3mentioning
confidence: 99%
“…25 Several studies have also shown that B7-H3 overexpression is associated with tumor progression, metastatic potential and a poor prognosis. [26][27][28][29] The immunemodulatory functions of B7-H3 remain controversial, with data supporting both stimulatory and inhibitory roles in T cell immunity in different model systems. 30 A monoclonal antibody (mAb) recognizing B7-H3 is being used to treat refractory pediatric brain cancers and thus far the clinical trial has yielded safe and promising results.…”
Section: Introductionmentioning
confidence: 99%
“…B7-H3 (CD276) is a checkpoint molecule expressed at high levels on many pediatric solid tumors including neuroblastoma ( 128 131 ). It plays a role in immune evasion ( 132 ) and metastatic potential ( 133 ), and overexpression correlates with poor prognosis in many cancers ( 134 ). These characteristics have made B7-H3 an attractive target for immunotherapeutic strategies, and early phase clinical trials with monoclonal antibodies have demonstrated encouraging results in both neuroblastoma and other malignancies ( 135 137 ).…”
Section: Challenges In Targeting Neuroblastoma With Car T Cellsmentioning
confidence: 99%